2010
DOI: 10.1021/nn1008897
|View full text |Cite
|
Sign up to set email alerts
|

Water-Dispersible Magnetite-Reduced Graphene Oxide Composites for Arsenic Removal

Abstract: Magnetite-graphene hybrids have been synthesized via a chemical reaction with a magnetite particle size of approximately 10 nm. The composites are superparamagnetic at room temperature and can be separated by an external magnetic field. As compared to bare magnetite particles, the hybrids show a high binding capacity for As(III) and As(V), whose presence in the drinking water in wide areas of South Asia has been a huge problem. Their high binding capacity is due to the increased adsorption sites in the M-RGO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

57
1,002
5
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,894 publications
(1,068 citation statements)
references
References 44 publications
57
1,002
5
4
Order By: Relevance
“…Due to their large theoretical specific surface area, remarkable electronic properties and high ability of modification, potential environmental applications of G as 0008-6223/$ -see front matter Ó 2012 Elsevier Ltd. All rights reserved. http://dx.doi.org/10.1016/j.carbon.2012.08.024 superior adsorbent have been recognized for removal of organic and inorganic contaminants from water and gases [6][7][8][9][10][11][12][13][14]. For example, it was found that sulfonated G was one of the most effective adsorbents for naphthalene and 1-naphthol [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their large theoretical specific surface area, remarkable electronic properties and high ability of modification, potential environmental applications of G as 0008-6223/$ -see front matter Ó 2012 Elsevier Ltd. All rights reserved. http://dx.doi.org/10.1016/j.carbon.2012.08.024 superior adsorbent have been recognized for removal of organic and inorganic contaminants from water and gases [6][7][8][9][10][11][12][13][14]. For example, it was found that sulfonated G was one of the most effective adsorbents for naphthalene and 1-naphthol [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] The rst use of functionalized graphene as an ionic water remediation adsorbent was conducted by Chandra et al who showed that arsenic could be removed easily from contaminated water. 36 Arsenic which exists in water as arsenite and arsenate ions is one of the most toxic and carcinogenic chemical elements when consumed in quantities above 10 parts per billion. In this study a water dispersible magnetite Fe 3 O 4 -rGO composite was synthesized by the simultaneous reduction of GO, FeCl 2 and FeCl 3 .…”
Section: Water Remediation By Adsorptionmentioning
confidence: 99%
“…36 Humera et al reported that iron decorated graphene sheets can be used for the removal of Cr(VI) from water through the catalytic reduction of Cr(VI) to Cr(III). 40 Zhu et al synthesized graphene decorated with core@double-shell nanoparticles, where the core is crystalline iron, the outer shell iron oxide and the external shell amorphous Si-S-O.…”
Section: Water Remediation By Adsorptionmentioning
confidence: 99%
“…Graphite oxide-based or graphene-based materials are known to be useful for water purification, toxic gas removal and ammonia adsorption applications [19][20][21]. Graphite oxide which possesses oxygen functional groups attached on both sides of the surface received attention due to its ability to modify the physical properties and surface chemistry to enhance the interactions with target molecules [22].…”
Section: Introductionmentioning
confidence: 99%